Decentralized controlled charging and vehicle-to-grid solution for voltage regulation in low voltage distribution systems - Zdraveski, Vasko; Angelov, Jordanco; Krstevski, Petar; Mateska, Aleksandra Krkoleva; Vuletic, Jovica; Todorovski, Mirko (Walter de Gruyter GmbH, 2022)
Abstract This paper offers affordable controlled charging and a vehicle-to-grid solution that uses a non-smart power meter. Additional communication infrastructure in the low-voltage distribution network is not needed. Ladder logic control is developed to be easily implemented by any commercial programmable logic controller. The voltage values measured by the power meter and electric vehicle battery state of charge are the decision variables. A validity check based on the Monte Carlo method is conducted to test the effectiveness of the proposed solution. Electric vehicle charging requirements are simulated based on travel surveys. The results demonstrate the effectiveness of the proposed solution. The voltage level is kept within acceptable limits according to the power quality standard EN50160. One may argue that there is a mismatch between the rate of penetration of electric vehicles and the level of smart grid implementation, especially in developing countries with higher rates of wealth inequality. Therefore, the methodology presented in this paper can be seen as an affordable mid-way solution that will help distribution system operators in developing countries prepare for higher penetration levels of EVs.
Keywords: electric vehicle, controlled charging, vehicle to grid, Monte Carlo, power meter